Implementation of a youth‐adult partnership model in youth mental health systems research: Challenges and successes. (14th March 2017) - Heffernan, Olivia S.; Herzog, Tyson M.; Schiralli, Jordana E.; Hawke, Lisa D.; Chaim, Gloria; Henderson, Joanna L.
Abstract: Background: By integrating Youth–Adult Partnerships (Y‐APs) in organizational decision making and programming in health‐care settings, youth can be engaged in decisions that affect them in a way that draws on their unique skills and expertise. Despite challenges, Y‐APs can have many benefits for youth and adults alike, as well as for the programmes and initiatives that they undertake together. Objective: This article describes the development, implementation and success of a Y‐AP initiative at the McCain Centre at the Centre for Addiction and Mental Health, a large urban hospital. Method: The McCain Y‐AP implementation model was developed based on the existing literature, guided by the team's progressive experience. The development and implementation procedure is described, with indicators of the model's success and recommendations for organizations interested integrating youth engagement. Results: The McCain Y‐AP has integrated youth into a wide range of mental health and substance use‐related initiatives, including research projects, conferences and educational presentations. The model of youth engagement is flexible to include varying degrees of involvement, allowing youth to contribute in ways that fit their availability, interest and skills. Youth satisfaction has been strong and both the youth and adult partners have learned from the experience. Discussion: Through the McCain Y‐AP initiative, youth engagement has helped advance numerous initiatives in a variety of ways. Flexible engagement, multifaceted mentorship, reciprocal learning and authentic decision making have led to a successful partnership that has provided opportunities for growth for all those involved. Health‐care organizations interested in engaging youth can learn from the McCain Y‐AP experience to guide their engagement initiatives and maximize success.